Possible origin of ferromagnetism in antiferromagnetic orthorhombic-YFeO3: A first-principles study. Issue 12 (15th August 2018) - Warshi, M. Kamal; Mishra, Vikash; Mishra, Vinayak; Kumar, Rajesh; Sagdeo, P.R.
Abstract: Rare-earth orthoferrites (RFeO3 ) are well-known for the antiferromagnetic ground state. However, some of the recent experimental results suggest that the few members of RFeO3 family possess ferromagnetism. In the present investigation we report the possible origin of ferromagnetism in antiferromagnetic YFeO3 using density functional theory. For this purpose, we have considered pure as well as self-doping in YFeO3 i.e. by considering the point defect at Y, Fe and O sites. Our finding suggests that the point defects in YFeO3 results in the mixed-valence state of Fe, which may result in ferromagnetism through Zener double exchange mechanism.